407 Effects of calcium-ammonium nitrate on in vitro ruminal fermentation using a wheat forage based substrate - Doblado, Andrea O (J Anim Sci, 2019)
A randomized complete block design was used to evaluate in vitro ruminal total gas and methane production, N-NH(3) concentration, and digestibility of wheat forage when incubated with calcium-ammonium nitrate (CAN). The in vitro fermentation consisted of 50 mL of a 4:1 buffer:ruminal fluid inoculum and 0.7 g of substrate [DM; wheat (Triticum aestivum; 100%) or wheat:corn (88:12)] incubated for 48 h. Batches were incubated on 4 separate days. Treatments included: 1) wheat (W); 2) wheat + corn (WC); 3) WC + 2% CAN in the substrate DM (WCN); and 4) WC + 0.67% UREA in the substrate DM (WCU). Treatments WCN and WCU were isonitrogenous. In vitro organic matter digestibility (IVOMD) was determined after incubation for 48 h with inoculum, followed by a 48 h incubation with HCl and pepsin solutions. Data were analyzed using the MIXED procedure of SAS with the fixed effect of treatment and random effect of day (block). Batch was considered the experimental unit. Total gas production was reduced by WCN compared with WCU (P = 0.049) and WC (P = 0.001). The addition of corn without NPN increased (P = 0.004) total gas production compared to wheat. An increased (P = 0.009) IVOMD was observed for WC compared to W, while no differences (P = 0.416) were observed between WCN and WCU. Ammonia-N concentration was not different (P = 0.463) between WCN and WCU; and the inclusion of NPN increased (P ≤ 0.026) NH(3)-N concentration compared to W. Methane production (mmol/g OM fermented) was lesser (P < 0.001) for WCN compared to WCU. Total VFA concentration and acetate:propionate were not affected by treatment (P > 0.05). Therefore, CAN can potentially be used as a NPN source with the additional benefit of in vitro methane mitigation without negatively affecting IVOMD or total VFA concentration.